A rare case report of Eagle’s syndrome complicated with chronic mouth opening, its management and complete rehabilitation; dental perspective - Kumar, A. Navin; Kumar, Bhushan; Dua, Gaurav; Mehta, Sandeep (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Eagle’s syndrome is a rare condition of either elongated styloid process or ossification of its ligaments; which is less appreciated and often ignored condition by clinicians because of its vague symptoms which can be easily confused with other oral or paraoral conditions presenting with similar signs and symptoms. Since it is not a routine clinical problem, it is not given the first priority thought while diagnosing such a case; especially in the absence of sound clinical knowledge and good radiographs. This article is aimed to summarize unusual clinical presentations, diagnosis and standardized tonsil-sparing trans-oral surgical approach for Eagle’s Syndrome case and its unique postoperative management. A 80 years old female patient presented with the tendency of uncontrolled wide mouth opening with severe pain in both ears, temporal region; submandibular area extending up to back of neck with intensity on right side. The patient was diagnosed as a case of the Eagle’s syndrome with a unique finding of pain relief on wide mouth opening. The patient was operated for bilateral styloidectomy followed by postsurgical rehabilitation with custom made chin cup appliance and mouth opening exercises.